2021
DOI: 10.1016/j.physa.2021.126014
|View full text |Cite
|
Sign up to set email alerts
|

A random walk Monte Carlo simulation study of COVID-19-like infection spread

Abstract: Recent analysis of early COVID-19 data from China showed that the number of confirmed cases followed a subexponential power-law increase, with a growth exponent of around 2.2 (Maier and Brockmann, 2020). The power-law behavior was attributed to a combination of effective containment and mitigation measures employed as well as behavioral changes by the population. In this work, we report a random walk Monte Carlo simulation study of proximity-based infection spread. Control interventions such as lockdown measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Such control interventions prevent a homogeneous mixing ( Fofana and Hurford, 2017 ) of the population, which if unchecked would lead to exponential growth, provided there is no depletion of the susceptible population ( Bailey, 1975 ). Our simulations ( Triambak and Mahapatra, 2021 ) further showed that the minimum growth exponent obtained under the most stringent mobility restrictions is quadratic growth . More realistically one would expect growth exponents that are slightly higher than 2, under the most effective containment scenarios ( Maier and Brockmann, 2020 , Triambak and Mahapatra, 2021 ).…”
Section: Logistic Growth Modelsmentioning
confidence: 53%
See 4 more Smart Citations
“…Such control interventions prevent a homogeneous mixing ( Fofana and Hurford, 2017 ) of the population, which if unchecked would lead to exponential growth, provided there is no depletion of the susceptible population ( Bailey, 1975 ). Our simulations ( Triambak and Mahapatra, 2021 ) further showed that the minimum growth exponent obtained under the most stringent mobility restrictions is quadratic growth . More realistically one would expect growth exponents that are slightly higher than 2, under the most effective containment scenarios ( Maier and Brockmann, 2020 , Triambak and Mahapatra, 2021 ).…”
Section: Logistic Growth Modelsmentioning
confidence: 53%
“…Our simulations ( Triambak and Mahapatra, 2021 ) further showed that the minimum growth exponent obtained under the most stringent mobility restrictions is quadratic growth . More realistically one would expect growth exponents that are slightly higher than 2, under the most effective containment scenarios ( Maier and Brockmann, 2020 , Triambak and Mahapatra, 2021 ). It is reasonable to expect that during the first wave of the pandemic (in 2020) most countries followed similar contaiment strategies at various levels to counter the spread of COVID-19 within their populace.…”
Section: Logistic Growth Modelsmentioning
confidence: 53%
See 3 more Smart Citations